Answer:
The solved given expression is
[tex]\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}=\frac{-96x}{7}[/tex]
Step-by-step explanation:
Given expression is [tex]\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}[/tex]
To solve the given expression :
[tex]\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}[/tex]
[tex]=\frac{-4+4+2x}{7}-14x[/tex]
[tex]=\frac{0+2x}{7}-14x[/tex]
[tex]=\frac{2x}{7}-14x[/tex]
[tex]=\frac{2x-14x(7)}{7}[/tex]
[tex]=\frac{2x-98x}{7}[/tex]
[tex]=\frac{-96x}{7}[/tex]
Therefore [tex]\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}=\frac{-96x}{7}[/tex]
Therefore the solved given expression is
[tex]\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}=\frac{-96x}{7}[/tex]